Optimal Monetary Policy in an Optimizing Stochastic Dynamic Model with Sticky Prices - Michael Gail (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2000)
Recently macroeconomic researchers have begun studying models of optimal monetary policy within the Real Business Cycle (RBC) framework. A standard RBC model is augmented by New Keynesian elements like sticky prices and monopolistically competitive firms. The monetary authority acts as a social planner maximizing the utility of a representative agent while at the same time taking care of the optimal price setting behavior of the firms via an implementation constraint. King/Wolman (1999) analyze the outcome of such a model with respect to the appropriate monetary policy of the central bank. They conclude that the central bank achieves a complete stabilization of the price level. Inflation is not only constant at the steady state but also through time. It is shown that this very special result does not hold under alternative preference specifications that allow for a richer set of substitution effects between consumption and labor.
Keywords: E52; 330; Monetary Policy Rules; New Neoclassical Synthesis; Sticky Prices; Real Business Cycle; Geldpolitik; Geldpolitisches Ziel; Neue klassische Makroökonomik; Real Business Cycle; Preisrigidität; Dynamische Optimierung; Theorie